O roli i znaczeniu funkcjonalnej analizy ekonomicznej w zarządzaniu przedsiębiorstwem - Duraj, Jan (About the Role and Meaning of Functional Economic Analysis in Management, 2005)
Economic analysis of company possesses at least threefold character. It is as tool and metafunction of managements and system of methods of estimation. It preference part and meaning is reflected mostly in processes of prognosting, deciding and controlling. Functional economic analysis is of special kind tool and system of methods of estimation oriented towards mission and last aim. It permits create of mission and of aim final firms of principle base of estimation of efficiency and rationalities its activities in functional, nonfunctional and nonfunctional dimensions.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1060, s. 95-102